PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK MENGGUNAKAN MODEL INKUIRI UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA PEMBELAJARAN IPA SD - Marfilinda, Riri; Apfani, Sry; Zuleni, Elva (Study program PGSD FKIP Universitas Bung Hatta, 2025)
This research is motivated by the ineffectiveness of the teaching materials circulating in improving students' critical thinking skills at Elementary School. This study aims to (1) describe the criteria for the development of inquiry-based LKPD; (2) Knowing the eligibility criteria of inquiry-based LKPD and (3) Knowing the improvement of critical thinking skills using the developed LKPD. This type of research is research and development using a 4-D model which consists of the defining, design, development and dissemination stages. The results of development and research show that (1) The characteristics of inquiry-based LKPD include the stages of fostering responsive activities, posing problems, asking questions, formulating hypotheses, testing hypotheses and drawing conclusions; (2) The LKPD eligibility criteria based on validity value 0f 3.67 (very valid) and practicality value of teacher and students or 3,5 and 3,6 (Excellent) and (3) Worksheet There was an increase in students' critical thinking skills with an N-gain score of 0.68 (medium category). Based on these results it can be concluded that the student worksheet based on inquiry is feasible, practical, and effective in improving students' critical thinking skills in Science Learning at elementary school.